ARE WE TRAINING MEDICAL STUDENTS TO MANAGE AUTONOMIC DYSREFLEXIA IN SPINAL CORD INJURY? A STUDY - ALfallaj, Muath Ibrahim; Salati, Sajad Ahmad (Sanamed, 2025)
Background: Autonomic dysreflexia (AD) is a potentially life-threatening complication of spinal cord injury (SCI), characterized by sudden, paroxysmal episodes of hypertension. Healthcare professionals and family members caring for individuals with SCI must be able to recognize and manage AD promptly and appropriately. This study aimed to assess the level of knowledge about AD among final-year medical students, evaluate their preparedness to manage AD, and highlight the importance of educating families of SCI patients on its recognition and management. Methods: A questionnaire-based, descriptive cross-sectional study was conducted among final-year (MD-4) medical students at the College of Medicine, Qassim University. Data were collected, cleaned, and analyzed using Microsoft Excel 2021. Students were then categorized into three groups based on their knowledge level: poor, fair, and good. Results: Significant gaps were identified in students’ knowledge of AD. Out of 68 students initially surveyed, 24 (35.3%) had not heard of AD and were excluded. Among the 44 participants included in the final analysis, scores ranged from 4 to 12 out of a maximum of 21, with a mean score of 7.02 (33.4%). A total of 27 students (61%) were classified as having poor knowledge, and 17 (39%) as fair. None of the students qualified for the “good” knowledge category. Conclusions: The findings underscore the need for incorporating autonomic dysreflexia into the undergraduate medical curriculum. Early education would ensure that medical graduates are better prepared to manage AD and can help prevent complications by educating patients’ families.